Identifying the true structure and origin of the water-quench induced hydride phase in Zr-2.5Nb alloy. (December 2021) - Long, Fei; Luo, Yu; Badr, Nima N.; Shiman, Oksana; Topping, Matthew; Persaud, Suraj Y.; Yao, Zhongwen; Béland, Laurent K.; Daymond, Mark R.
Abstract: The crystal structure of the hydride induced by water quenching in hydrided Zr-2.5Nb pressure tube was identified by a combined approach of synchrotron x-ray diffraction and TEM nano-beam electron diffraction, coupled with density functional theory. It has been found that the hydrides experimentally characterized have the same face-centered tetragonal lattice structure as that of the γ-phase, however the hydrogen atoms did not show evidence of ordering. The quenched hydrides subsequently transformed into both ordered face-centered tetragonal (i.e., γ-phase) as well as δ-phase during a one-year room temperature aging, implying a metastable nature; therefore, we argue it is appropriate to identify these initial quenched hydrides as γ′ instead of the γ hydride the majority of literature has used in the past. The amount of γ′ phase is found to increase with the temperature at which the sample is quenched from, while the amount of δ phase changed inversely. In-situ heating experiments with synchrotron diffraction on samples with various prior heat treatments were also conducted; the γ′ phase was found to be present at temperatures up to 278˚C. Transformation of γ′ into δ hydride was found to occur upon heating, confirming the relative stability of the two phases. The origin of the γ′ phase is compatible with the newly confirmed Zr-H phase diagram where γ-hydride exists as the low temperature stable phase. Graphical abstract: Image, graphical abstract